An Analysis of Speech Functions Realizations on the Electronics and Furniture Billboard Texts - Muhammad Hasyimsyah Batubara (Jurnal Ilmu Komunikasi, 2020)
This research analyzes the dominant category and to explains the tendency to use the speech functions model in electronics and furniture billboard texts. The research method used descriptive qualitative. Data was collected by applying documentary techniques from 32 commercial electronics and furniture billboard texts (headline, subhead, slogan, and images) in Medan. The results of the research found the four speech functions were used, the statement model was 62.5%, the question model was 3%, the command model was 18.8%, and the offered model was 15.6%. The statement model is used as the dominant one, in line with the billboard text pattern, where it is assumed to only see the display of billboard text and images with a duration of 5-7 seconds while driving. The substance of this research contributes in the form of new policy recommendations for advertisers to pay attention to speech in advertising communication messages conveyed correctly, precisely, and firmly. Advertisers are directed to pay more attention to the concept of the speech function with an efficient, effective, and hypnotic approach to readers.